PENGGUNAAN ZOLETIL DAN KETAMINE UNTUK ANESTESIA PADA FELIDAE - I Komang Wiarsa Sardjana (The East Java Biological Society, 2003)
Zoletil and ketamine as a non barbiturat anaesthetic can be administered by the intramuscular route in Felidae a specially in the wild animals and pets. Seven Felidaeof the wild animals there were five the Lions (Panthera leo) and two the White tigers (Panthera tigris tigris) of the Surabaya Zoological Garden have of Zoletil with dose 5 mg/kg body weight and seven Cats of Veterinary Hospital of Faculty of Veterinary Medicine of airlangga was used Ketamine as anaesthetic with dose 20 mg/Kg body weight. All the animals have injected Atropin sulfate with dose 0.1 mg/Kg body weight intramuscular as a premedication. The result of this study of Zoletil in Felidae are shown that the animals have not in respiratory depression and during anaesthesia have done the body temperature means about 36.9º C, Pulsus rate is 100.8 times/minutes and Respiration rate is 21.7times/minutes. The studi of Ketamine the data shown during anaesthesia the means of the body temperature of the cats is 38.4º C with pulsus rate is 85.1 times/minutes and respiration rate is 41.1 time/minutes. We have assumed that study of the drug have a great effect of the animals in practice look like in cats or the wild animals for restraint or anaesthesia of short duration.